2003
DOI: 10.1089/088922203322493021
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free HIV Type 1 Infection is Restricted in the Human Trophoblast Choriocarcinoma BeWo Cell Line, Even with Expression of CD4, CXCR4 and CCR5

Abstract: The restriction of cell-free HIV-1 infection has been demonstrated in placental trophoblast choriocarcinoma BeWo cells. We tried to determine the level of the viral replication cycle at which this restriction occurs. BeWo cells produce infectious viruses after transfection with HIV-1 plasmids, independently of viral tropism. CCR5 and CXCR4, but not the CD4 molecule, were detected at the cell surface. We therefore derived CD4-expressing clones from transfected BeWo cells. Cell-free virus infection of these clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 53 publications
1
32
0
1
Order By: Relevance
“…It is now well established that infection of primary trophoblasts or of trophoblastderived cell lines with cell-free HIV-1 is poorly or not at all productive (7,15,32). Our results showing that PSF increased viral production in these cells inoculated with HIV-1-infected PBMCs suggested that PSF could also alter the resistance of BeWo cells to cell-free virus.…”
Section: Resultsmentioning
confidence: 53%
“…It is now well established that infection of primary trophoblasts or of trophoblastderived cell lines with cell-free HIV-1 is poorly or not at all productive (7,15,32). Our results showing that PSF increased viral production in these cells inoculated with HIV-1-infected PBMCs suggested that PSF could also alter the resistance of BeWo cells to cell-free virus.…”
Section: Resultsmentioning
confidence: 53%
“…19 Trophoblast cells are also able to produce chemokines and their receptors. 20,21 The role of these processes in materno-foetal transmission of T. gondii is not clear. However, immunohistochemical studies in a rat model of congenital infection showed T. gondii multiplication in intact trophoblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…For cell-free virus infections of MDM, the R5 tropic primary isolate HIV-1 BaL [61] was used. The viral stock was prepared in MDM.…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase reporter viruses were produced as previously described [61] by transiently cotransfecting (Lipofectamine 2000, Invitrogen, USA) 293T cells with the proviral pNL-Luc-E-R+ vector [62], which lacks the env gene and has the firefly luciferase gene inserted into the nef gene, and the expression vector pCMV harbors the gene coding for either the VSV-G envelope protein or the HIV-1 R5 (BaL) envelope protein. 293T cells were also transfected only with pNL-Luc-E-R+ (Denv pseudotype).…”
Section: Methodsmentioning
confidence: 99%